The Effect of Capital Intensity, Profitability, and Leverage on Tax Avoidance - Safitra, Indira Nur; Totanan, Chalarce (International Journal of Science and Society, 2025)
This study uses three independent variables capital intensity, profitability, and leverage as its primary emphasis to investigate tax avoidance behavior in food and beverage manufacturing companies listed on the Indonesian Stock Exchange for the 2019-2022 period. The secondary data used in this study includes financial information obtained from annual and financial reports with favorable profit margins. 30 samples were previously selected using the purposive sampling approach out of a total of 120 data. The results of the study show that capital intensity and leverage have no effects on tax avoidance. Meanwhile, tax avoidance is significantly impacted negatively by profitability. Leverage, profitability, and capital intensity all have an impact on tax avoidance at the same time.